Development and Identification of a Novel Anti-HIV-1 Peptide Derived by Modification of the N-Terminal Domain of HIV-1 Integrase - Sala, Marina; Spensiero, Antonia; Esposito, Francesca; Scala, Maria C.; Vernieri, Ermelinda; Bertamino, Alessia; Manfra, Michele; Carotenuto, Alfonso; Grieco, Paolo; Novellino, Ettore; Cadeddu, Marta; Tramontano, Enzo; et al. (Frontiers in Microbiology, 2016)
The viral enzyme integrase (IN) is essential for the replication of human immunodeficiency virus type 1 (HIV-1) and represents an important target for the development of new antiretroviral drugs. In this study, we focused on the N-terminal domain (NTD), which is mainly involved into protein oligomerization process, for the development and synthesis of a library of overlapping peptide sequences, with specific length and specific offset covering the entire native protein sequence NTD IN 1-50. The most potent fragment, VVAKEIVAH (peptide 18), which includes a His residue instead of the natural Ser at position 39, inhibits the HIV-1 IN activity with an IC50 value of 4.5 M. Amino acid substitution analysis on this peptide revealed essential residues for activity and allowed us to identify two nonapeptides (peptides 24 and 25), that show a potency of inhibition similar to the one of peptide 18. Interestingly, peptide 18 does not interfere with the dynamic interplay between IN subunits, while peptides 24 and 25 modulated these interactions in different manners. In fact, peptide 24 inhibited the IN-IN dimerization, while peptide 25 promoted IN multimerization, with IC50 values of 32 and 4.8 µM, respectively. In addition, peptide 25 has shown to have selective anti-infective cell activity for HIV-1. These results confirmed peptide 25 as a hit for further development of new chemotherapeutic agents against HIV-1.